2020
DOI: 10.1111/liv.14617
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced ultrasound liver imaging reporting and data system for diagnosing hepatocellular carcinoma: A meta‐analysis

Abstract: Background & aims: Contrast-enhanced ultrasound (CEUS) Liver Imaging Reporting and Data System (LI-RADS) is a comprehensive system for standardizing CEUS at high risk for hepatocellular carcinoma (HCC). We performed a meta-analysis to determine the diagnostic performance of the CEUS LR-5 for HCC and the pooled proportions of HCCs in each CEUS LI-RADS category. Methods: We searched multiple databases for studies reporting the diagnostic accuracy of the CEUS LI-RADS. Random-effects model was used to determine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Our meta-analysis found that the pooled sensitivity and specificity for diagnosing HCC of CEUS LR5 was 69% and 93%, respectively, which was quite similar to those summary estimates of CT/MRI LR5 (sensitivity 67% and specificity 93%). A study conducted by Shin et al [16] suggested that the diagnostic performances for diagnosing HCC of LI-RADS with CEUS and CT/MRI can be compared. In our study, there was no statistical difference between CEUS LR5 and CT/MRI LR5 in the overall diagnostic accuracy for diagnosing HCC (p = 0.55), but a specificity of 93% for HCC diagnosis of LR5 was lower than that preconceived in the LI-RADS algorithm (definitely HCC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta-analysis found that the pooled sensitivity and specificity for diagnosing HCC of CEUS LR5 was 69% and 93%, respectively, which was quite similar to those summary estimates of CT/MRI LR5 (sensitivity 67% and specificity 93%). A study conducted by Shin et al [16] suggested that the diagnostic performances for diagnosing HCC of LI-RADS with CEUS and CT/MRI can be compared. In our study, there was no statistical difference between CEUS LR5 and CT/MRI LR5 in the overall diagnostic accuracy for diagnosing HCC (p = 0.55), but a specificity of 93% for HCC diagnosis of LR5 was lower than that preconceived in the LI-RADS algorithm (definitely HCC).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review explored the pooled proportion of HCC and overall malignancy in each LR based on CT and MRI [14]. Another two meta-analyses determined the sensitivity and specificity of LR5 for diagnosing HCC using CT/MRI LI-RADS and CEUS LI-RADS, respectively [15,16]. Kim et al focused on the probability of HCC and OM in the LRM based on MRI [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is a non-invasive localization method with the advantages of low price, repeatability, no radiation damage, and high sensitivity. However, there are blind areas, which are difficult to detect, which are not only affected by the background of other liver diseases but also by the performance of the equipment and the anatomical knowledge and experience and operation of the operator [ 10 ]. The process of abundant blood supply and angiogenesis in the focus of liver cancer is exuberant, and a large number of neovascularization can provide nutrients for the growth of tumor cells.…”
Section: Clinical Data Analysismentioning
confidence: 99%
“…High specificity of LR-5 for HCC and high sensitivity of LR-M for non-HCC malignancies are required to meet the purpose of LI-RADS on achieving accurate diagnosis, which helps to choose the proper treatments. Several previous studies have proved that there were no significant difference in the specificity of LR-5 for HCC between CEUS LI-RADS and CT/MR LI-RADS (18,19,21), however, studies directly focusing on the sensitivity of LR-M for non-HCC malignancies between these two algorithms remained limited. Thus, this retrospective study investigated the sensitivity of LR-M for non-HCC malignancies in a relatively large sample of non-HCC malignancies.…”
Section: Discussionmentioning
confidence: 99%